2017
DOI: 10.1016/j.toxrep.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Is Andrographis paniculata extract and andrographolide anaphylactic?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…A. paniculata is the well-known medicinal plant, and the safety of using A. paniculata as a traditional medicine is supported by the results of the present study. Moreover, the report demonstrating that A. paniculata has no anaphylactic reaction which is a serious and potential deadly adverse effect [20] reinforces the safety of A. paniculata used. Based on a variety of pharmacological actions on A. paniculata , the possible application of standardized FTLEE of A. paniculata can be diverse including as an alternative or adjuvant treatment for cholangiocarcinoma and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 92%
“…A. paniculata is the well-known medicinal plant, and the safety of using A. paniculata as a traditional medicine is supported by the results of the present study. Moreover, the report demonstrating that A. paniculata has no anaphylactic reaction which is a serious and potential deadly adverse effect [20] reinforces the safety of A. paniculata used. Based on a variety of pharmacological actions on A. paniculata , the possible application of standardized FTLEE of A. paniculata can be diverse including as an alternative or adjuvant treatment for cholangiocarcinoma and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 92%
“…Considering previous reports, mild-to moderate allergic reactions have been observed, especially with higher doses of andrographolide. In-vitro and in-vivo studies have shown that high-dose andrographolide induced histamine and LTC4 release in IgE sensitized RBL-2H3 cells, and release of tryptase, β-hexosaminidase and LTC4 tested through a non-IgE mediated pathway indicating it might induce anaphylactoid reactions [30]. Dysgeusia could be attributed to andrographolide bitterness [31].…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous reports, mild-to moderate allergic reactions have been observed, especially with higher doses of andrographolide. In-vitro and in-vivo studies have shown that high-dose andrographolide induced histamine and LTC4 release in IgE sensitized RBL-2H3 cells, and release of tryptase, β-hexosaminidase and LTC4 tested through a non-IgE mediated pathway indicating it might induce anaphylactoid reactions [30]. Dysgeusia could be attributed to andrographolide bitterness [31].…”
Section: Discussionmentioning
confidence: 99%